Efficiency Challenges Amid Budget Success in Indonesia: Tantangan Efisiensi di Tengah Keberhasilan Anggaran di Indonesia - Intan Setyaningrum; Nihlatul Qudus Sukma Nirwana (Academia Open, 2024)
This study assesses the budget implementation of the Sidoarjo Regency Government from 2019 to 2022, focusing on effectiveness, efficiency, and economic performance. Using a descriptive quantitative approach with document analysis, the findings indicate that while the government has met economic criteria and shown improved effectiveness, efficiency has been less satisfactory, particularly in 2022. Despite surpassing budget revenue targets, inefficiencies arose due to higher expenditures than revenues. The study highlights the need for better budget management and resource allocation to enhance overall performance. Highlight: Economic Criteria Met: Consistent economic performance over four years. Improved Effectiveness: Surpassed budget revenue targets. Efficiency Issues: Lower efficiency, especially in 2022. Keyword: Budget implementation, effectiveness, efficiency, economic performance, Sidoarjo Regency